Energy Potential of Solar and Water Resources in Uzbekistan and Their Use - Bozarov Oybek Odilovich; Usarov Khamidillo Saydullayevich; Saidullayeva Saidakhon Rakhmanovna (International Journal on Integrated Education, 2022)
In this article, the hydropower potential of solar energy and water resources in Uzbekistan and the state of their use are studied, and plans for the effective use of these energies in the future are reflected.